PENGARUH FAKTOR LINGKUNGAN DAN PERILAKU MEROKOK TERHADAP KEJADIAN ISPA PADA BALITA - Utami, Utami; Rosdiana, Rosdiana; Assagaff, Farha (Ensiklopedia of Journal, 2024)
Based on data from Puskesmas Pustu Panca Mukti for the period January - September 2020, 341 cases were found in toddlers aged 1-5 years, and the incidence of ARI disease ranks first in the list of the 10 most common diseases at Puskesmas Pustu Panca Mukti. Based on an initial survey conducted by researchers around the working area of Puskesmas Pustu Panca Mukti, researchers found dense occupancy, the distance between houses which is only limited by walls and the environment around the house is not clean. The purpose of the study was to determine the effect of environmental factors and smoking behavior on the incidence of ARI in toddlers. This type of research uses quantitative with a cross sectional approach. The research was conducted in July-August 2023 in the Tanjung Berlian Health Center work area. The research sample used random sampling which amounted to 77 people. The results showed that there was a relationship between the physical condition of ventilation (p value: 0.000) and family smoking behavior (p value: 0.000) with the incidence of ARI in toddlers. It is recommended that families and communities can increase awareness not to smoke when there are toddlers because it will lead to ARI disease and the Puskesmas pay more attention to family problems by conducting counseling in the form of the importance of family function and prevention of ARI incidence.  Keywords: Toddlers, ARI, Smoking, Ventilation.